The usage of experimental learning strategy to develop vocabulary in the English language learning. - Buñay Quishpi, Jennifer Lucinda (2025)
Consider the obstacles imposed by traditional methods of teaching and learning English to act through interactive methods that promote a broad understanding in the acquisition of new words. The objective of this study was to evaluate the effectiveness of experiential learning strategies in the progress of English vocabulary in eighth grade students of the “Simón Rodríguez” Educational Unit. Two# questionnaires# were administered, one pre- and one #post-test, to determine the students' vocabulary level, limitations, and subsequent progress. The results show representative improvements in accuracy levels between 50 and 60%. This shows that experimental learning strategies allowed improving the understanding of vocabulary associated with the Vygotsky and Kolb theory. However, the research identified limiting factors such as sample size and previous knowledge of the students. It is necessary to develop other studies with different sample sizes, grades and educational units that allow for improved results. In conclusion, the effectiveness of experiential learning strategies for improving English vocabulary acquisition was illustrated. The results contributed to dynamic classes; student-centered learning helps students understand the meaning of newly acquired vocabulary, especially in improving English language education.